Paeonol Ameliorates Glucose and Lipid Metabolism in Experimental Diabetes by Activating Akt - Xu, Futian; Xiao, Haiming; Liu, Renbin; Yang, Yan; Zhang, Meng; Chen, Lihao; Chen, Zhiquan; Liu, Peiqing; Huang, Heqing (Frontiers in Pharmacology, 2019)
Our previous study proved that paeonol could lower blood glucose levels of diabetic mice. There are also a few reports of its potential use for diabetes treatment. However, the role of paeonol in regulating glucose and lipid metabolism in diabetes remains largely unknown. Considering the critical role of serine/threonine kinase B (Akt) in glucose and lipid metabolism, we explored whether paeonol could resist glucose and lipid metabolism disorders via Akt. Here, in diabetic mice, we found that paeonol attenuated fasting blood glucose, glycosylated serum protein, serum cholesterol and triglyceride, hepatic glycogen, cholesterol and triglyceride. Moreover, paeonol enhanced glucokinase (GCK) and low-density lipoprotein receptor (LDLR) protein expressions, and increased the phosphorylation level of Akt. In insulin-resistant HepG2 cells, paeonol increased glucose uptake but decreased lipid accumulation. What’s more, paeonol elevated LDLR and GCK expressions as well as Akt phosphorylation level, consistent with the in vivo results. Knockdown and inhibition experiments of Akt revealed that paeonol regulated LDLR and GCK levels through Akt. Molecular docking assay indicated the steady hydrogen bond formed between paeonol and Akt2. Experiments above suggested that paeonol ameliorated glucose and lipid metabolism disorders and the underlying mechanism was closely related to Akt.